The Role of Local Administration in Protecting the Environment in a Participatory Framework - Zaydi, Abdelaziz; Amir, Fahmi (Journal of Legal Studies and Researches, 2022)
This study works to adjust concepts related to environmental protection issues, and the role of the state in preserving the environment, which is exclusively reflected in the intervention of local administrative bodies in protecting the environment from pollution, due to their direct contact with reality. The environment, and this study works on embodying the idea of new local governance.